AFTER HARVEST QUALITATIVE AND QUANTITATIVE BEHAVIOUR OF SOME SUGAR BEET VARIETIES - M. A. Sarwar; F. Hussain; A. A. Chattha (Journal of Animal and Plant Sciences, 2008)
The studies reported here were undertaken at Sugarcane Research Institute Faisalabad during the crop season 2006-2007. Four sugarbeet varieties namely polyrex, polyplus, SD PAK 01/06 and SD PAK 02/06 were compared for weight losses, pol and sugar recovery after harvest while storing under shade and sun conditions for a period of six storage days. Statistically significant difference was recorded in all studied parameters. The maximum pol of samples stored under shade (16.19%) and sun (16.61%) was observed in SD PAK 01/06 and same trend was found in sugar recovery. Polyplus showed minimum weight losses, 10.55% and 11.97%, in sun and shade respectively. The experiment pointed out a direct relation of increasing weight losses with the increase in pol and sugar recovery as well as variable after harvest behaviour of four sugarbeet varieties with respect to three studied parameters.
Keywords: Qualitative; Quantitative; Behavior; Sugar beet.